2019
DOI: 10.1164/rccm.201805-0996oc
|View full text |Cite
|
Sign up to set email alerts
|

Underdetection and Undertreatment of Dyspnea in Critically Ill Patients

Abstract: Rationale: Dyspnea is a common and distressing physical symptom among patients in the ICU and may be underdetected and undertreated.Objectives: To determine the frequency of dyspnea relative to pain, the accuracy of nurses and personal caregiver dyspnea ratings relative to patient-reported dyspnea, and the relationship between nursedetected dyspnea and treatment.Methods: This was an observational study of patients (n = 138) hospitalized in a medical ICU (MICU). Nurses and patients' personal caregivers at the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 34 publications
(41 reference statements)
0
49
0
1
Order By: Relevance
“…The level of inspiratory effort during the first 3 days of ventilation was recently shown to predict the duration of ventilation and ICU admission [6]. Respiratory drive and effort are frequently elevated in patients with respiratory failure because of pain, anxiety, delirium, inadequate ventilatory assistance, and dyspnea [7, 8]. Therefore, patient inspiratory effort merits close attention during mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…The level of inspiratory effort during the first 3 days of ventilation was recently shown to predict the duration of ventilation and ICU admission [6]. Respiratory drive and effort are frequently elevated in patients with respiratory failure because of pain, anxiety, delirium, inadequate ventilatory assistance, and dyspnea [7, 8]. Therefore, patient inspiratory effort merits close attention during mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…38,45 However, numerous studies indicate minimal and often delayed opioid use. 7,46 One study showed that only 49% of patients with ILD receive opioids to manage dyspnea, despite improvement of symptoms in the study. 3 Opiates were initiated a median of 105 days before death in 88% of our home/hospice cohort; 82% of our home/hospice death cohort were prescribed oral mucosal opiates compared to 24% in the hospital death cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although dyspnea is not uncommon, published literature on the topic suggests that clinicians often underestimate its presence. [78][79][80] Binks et al 78 reported that significant breathing discomfort is as common as pain in mechanically ventilated subjects and that clinicians misjudge its occurrence. In a prospective, multi-center study, Haugdahl and colleagues 79 assessed agreement between physicians, nurses, and mechanically ventilated subjects' rated breathlessness during spontaneous breathing trials.…”
Section: Monitoring Dyspneamentioning
confidence: 99%
“…The results indicated that subjects reported more breathlessness after undergoing spontaneous breathing trials compared to assessments made by physicians and nurses. More recently, Gentzler et al 80 assessed the frequency of dyspnea relative to pain as well as the accuracy of nurses' and personal caregivers' dyspnea ratings relative to patient-reported dyspnea in subjects admitted to the medical ICU. The study results indicated that 47% of subjects reported moderate-to-severe dyspnea and 41% reported moderate to severe pain.…”
Section: Monitoring Dyspneamentioning
confidence: 99%